Transforming Therapy : Mental Health Practice and Cultural Change in Mexico - Duncan, Whitney L., 1980- (Book collections on Project MUSE., 2018)
"Oaxaca is known for many things--its indigenous groups, archaeological sites, crafts, and textiles--but not for mental health care. When one talks with Oaxacans about mental health, most say it's a taboo topic and that people there think you "have to be crazy to go to a psychologist." Yet throughout Oaxaca are signs advertising the services of a psicólogico; there are prominent conferences of mental health professionals; and self-help groups like Neurotics Anonymous thrive, where participants rise to say, "Hola, mi nombre es Raquel, y soy neurótica."How does one explain the recent growth of Euroamerican-style therapies in the region? Author Whitney L. Duncan analyzes this phenomenon of "psy-globalization" and develops a rich ethnography of its effects on Oaxacans' understandings of themselves and their emotions, ultimately showing how globalizing forms of care are transformative for and transformed by the local context. She also delves into the mental health impacts of migration from Mexico to the United States, both for migrants who return and for the family members they leave behind. This book is a recipient of the Norman L. and Roselea J. Goldberg Prize from Vanderbilt University Press for the best book in the area of medicine"--Provided by publisher